Light sensitivity in euglena is provided by the eyespot. True or False?
True. Light sensitivity in euglena is provided by the eyespot.
stan_r|Points 772|
Question
Updated 2/3/2014 10:15:32 AM
Edited by andrewpallarca [2/3/2014 10:15:30 AM], Confirmed by andrewpallarca [2/3/2014 10:15:32 AM]
Rating

Questions asked by the same visitor
What are the terms in the expression x3 - 5x - 18 + 8x2? Solution: User: What are the terms in the expression x3 - 5x - 18 + 8x2? Solution:
Weegy: The answer is x=(1)/(2). [ 5-(x+2)=5x Multiply -1 by each term inside the parentheses (x+2). 5-(x)-(2)=5x Multiply -1 by the x inside the parentheses. 5-x-(2)=5x Multiply -1 by the 2 inside the parentheses. 5-x-2=5x Subtract 2 from 5 to get 3. 3-x=5x Since 5x contains the variable to solve for, move it to the left-hand side of the equation by subtracting 5x from both sides. 3-x-5x=0 According to the distributive property, for any numbers a, b, and c, a(b+c)=ab+ac and (b+c)a=ba+ca. Here, x is a factor of both -x and -5x. 3+(-1-5)x=0 Subtract 5 from -1 to get -6. 3+(-6)x=0 Remove the parentheses. 3-6x=0 Since 3 does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting 3 from both sides. -6x=-3 Divide each term in the equation by -6. -(6x)/(-6)=-(3)/(-6) Move the minus sign from the denominator to the front of the expression. -(-(6x)/(6))=-(3)/(-6) Cancel the common factor of 6 in -(6x)/(6). -(-( 6 x)/( 6 ))=-(3)/(-6) Remove the common factors that were cancelled out. -(-x)=-(3)/(-6) Multiply -1 by the -x inside the parentheses. -1*-x=-(3)/(-6) Multiply -1 by -x to get x. x=-(3)/(-6) Move the minus sign from the denominator to the front of the expression. x=-(-(3)/(6)) Cancel the common factor of 3 in -(3)/(6) since -(3)/(6)=((-1*3))/((2*3)). x=-(-( 3 )/(2 6 )) Remove the common factors that were cancelled out. x=-(-(1)/(2)) Multiply -1 by the -(1)/(2) inside the parentheses. x=-1*-(1)/(2) Multiply -1 by -1 to get 1. x=(1)/(2). Hope this helps. ] User: Score: Simplify 6(x + y) + (x - y). 6x 7x 7x + 6y 7x + 5y User: Simplify 6(x + y) + (x - y). Weegy: What is your question? :) User: Score: Simplify 6(x + 2) + 7. 6x + 9 6x + 15 6x + 19 Weegy: 6 x 7 = 42 ? User: Score: Simplify 6(x + 2) + 7. (More)
Question
Updated 6/30/2014 1:11:36 AM
6(x + y) + (x - y)

=6x+6y+x-y

=7x+5y
6(x+2)+7

=6x+12+7

=6x+19
27,181,522
*
Get answers from Weegy and a team of really smart live experts.
Popular Conversations
What is Amendments III?
Weegy: The First Amendment prohibits the making of any law respecting an establishment of religion, impeding the free ...
17. The two proposed plans for the Constitution agreed on? A. ...
Weegy: The two proposed plans for the Constitution agreed on having three branches of government. [ ] User: 18. ...
19% of 400
40 degrees Celsius In Fahrenheit? User: 41 degrees Fahrenheit is ...
Weegy: 41 Fahrenheit is 5 degrees Celsius. User: How to change 10 cubic feet into cubic inches?
S
L
P
P
Points 90 [Total 544] Ratings 0 Comments 90 Invitations 0 Offline
S
L
R
P
R
P
R
Points 74 [Total 534] Ratings 0 Comments 4 Invitations 7 Offline
S
Points 33 [Total 33] Ratings 0 Comments 3 Invitations 3 Offline
S
R
L
R
P
R
P
R
R
R
Points 30 [Total 852] Ratings 0 Comments 0 Invitations 3 Offline
S
Points 21 [Total 21] Ratings 2 Comments 1 Invitations 0 Offline
S
Points 16 [Total 33] Ratings 0 Comments 16 Invitations 0 Offline
S
Points 12 [Total 12] Ratings 0 Comments 12 Invitations 0 Offline
S
Points 10 [Total 40] Ratings 1 Comments 0 Invitations 0 Offline
S
Points 1 [Total 1] Ratings 0 Comments 1 Invitations 0 Offline
S
Points 1 [Total 1] Ratings 0 Comments 1 Invitations 0 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.